Solid State Synthesis of 4-Aryl-3,4-dihydropyrimidine-2-(1H)-ones - Meenakshi, Chandran; Christopher, Eliya (Asian Journal of Chemistry, 2010)
An efficient, solid state, microwave assisted synthesis of 4-aryl-3,4-dihydropyrimidine-2-(1H)-ones using zeolite 4A is reported in Biginelli, onepot, three component coupling reaction of 1,3-diketones, aldehydes and urea.